Literasi Digital, Massive Open Online Courses, dan Kecakapan Belajar Abad 21 Mahasiswa Generasi Milenial - Imam Fitri Rahmadi; Eti Hayati (BPSDMP Kominfo Jakarta, 2020)
Millennial generation students need to be equipped with adequate digital literacy in order to face the industrial revolution 4.0. Unfortunately, students' digital literacy particularly related to the 21st century learning abilities is relatively low. This article critically discusses digital literacy massive open online courses (DL-MOOCs) need developments in higher education, including; 1) the need of digital literacy for academic purposes; 2) the development of MOOCs around the world and in Indonesia; 3) 21st century learning abilities of millennial generation students. Study in this article is the result of preliminary research using literature review and survey methods involving 245 first-year millennial generation students. The results revealed that; 1) digital literacy for academic purposes is needed since ample digital information has been utilised as learning resources and the learning process in higher education have commonly conducted in a digital environment; 2) the development of MOOCs opens extensive opportunities to be used as a massive, open, and online learning platform to improve digital literacy of millennial generation students; and 3) 21st century learning abilities of millennial generation students are very low in the components of creative collaborator and innovative designer. These results indicate the urgency of MOOCs developments that focus on digital literacy for academic purposes. Mahasiswa generasi milenial perlu dibekali dengan literasi digital yang memadai dalam rangka menghadapi revolusi industri 4.0. Sayangnya, literasi digital mahasiswa terutama yang berkaitan dengan kecakapan belajar secara digital pada abad 21 masih tergolong rendah. Artikel ini mendiskusikan secara kritis kebutuhan pengembangan digital literacy massive open online courses (DL-MOOCs) di perguruan tinggi, meliputi; 1) kebutuhan literasi digital untuk keperluan akademik; 2) perkembangan MOOCs di dunia dan Indonesia; dan 3) kecakapan belajar abad 21 mahasiswa generasi milenial. Kajian dalam artikel merupakan hasil penelitian pendahuluan menggunakan metode kajian pustaka dan survei melibatkan 245 mahasiswa generasi milenial yang sedang menempuh perkuliahan pada tahun pertama. Hasil penelitian menunjukkan bahwa; 1) literasi digital untuk keperluan akademik sangat dibutuhkan karena hampir semua informasi yang dijadikan sumber belajar dan proses pembelajaran di perguruan tinggi sudah banyak dilakukan dalam lingkungan digital; 2) perkembangan MOOCs membuka kesempatan luas untuk dapat digunakan sebagai platform pembelajaran terbuka dan masif untuk meningkatkan literasi digital mahasiswa generasi milenial; dan 3) kecakapan belajar abad 21 mahasiswa generasi milenial masih sangat rendah pada komponen creative collaborator dan innovative designer. Hasil tersebut menunjukkan urgensi pengembangan MOOCs yang berfokus pada literasi digital untuk keperluan akademik.